Optimalisasi Pelayanan Ark (Account Representative Khusus) dalam Proses Akuisisi Pekerja Informal pada Program Jaminan Sosial Ketenagakerjaan di Kantor Cabang Surabaya Darmo - Sintya Rahma Sari; Vidya Imanuari Pertiwi (Masyarakat Ekonomi Syariah Bogor, 2025)
Optimisation of services in the informal participant acquisition process by ARK (Special Account Representative) is an important aspect in the effort to expand the informal segment and increase the number of informal participant acquisitions. Therefore, services that meet the needs of the community are needed. This research aims to describe and analyse how the services provided by ARK (Special Account Representative) in the acquisition process of informal workers in the employment social security program at the Surabaya Darmo branch office. The research method used in this research is a qualitative approach. Data collection techniques using primary and secondary data. Primary data obtained from active participation observation, interviews conducted with ARK employees at BPJS Surabaya Darmo branch office as many as five people and conducted in a semi-structured manner, documentation results obtained during the participant acquisition process in the field. While secondary data is obtained from the analysis of journal literature, books, and the internet that are relevant to the object and focus of research. The results of this study indicate that the Optimisation of ARK Services in the BPU Acquisition Process at Darmo Surabaya Branch Office can be seen from the five gaps according to Tjiptono's theory (2009: 267-272), namely, knowledge gap, standards gap, deliver gap, communication gap, and service gap and the results obtained that the services provided by ARK (Special Account Representative) at BPJS Ketenagakerjaan in the process of acquiring informal workers are optimal, but there is a need for continuous evaluation and optimisation of comprehensive service improvement. With these steps, it is expected that the participation of informal workers in the BPJS Ketenagakerjaan programme can increase significantly, so as to provide wider protection for informal worker groups.